Investigation of Photovoltaic Energy Yield on Tromsøya by Mapping Solar Potential in ArcGIS - Eikeland, Odin Foldvik (UiT The Arctic University of Norway, 2019)
To contribute to the reduction of greenhouse gas emissions, energy production from renewable energy resources should be markedly increased to supply the rising global energy demand (Marchant, 2018). This thesis investigates the solar energy potential in Tromsø which is used as a basis for estimating total energy yield from photovoltaic (PV) systems on rooftops. The energy yield is compared against energy load from Cruise ships visiting Tromsø to investigate the potential for supplying the ships with renewable, local produced PV solar energy to substitute the ships own production of energy. The aim of this thesis is to investigate the solar potential on Tromsøya by creating a solar map in ArcGIS. The solar map could be used as a basis for investigating energy yield from PV systems installed on buildings. The suitable areas for PV systems on Tromsøya were determined by qualified estimations based on building area statistics and utilization factors. The energy load from Cruise ships was estimated by using given information from Port of Kristiansand, the only harbor in Norway which offer the possibilities for shore power. This thesis has created the first 0.25-meter resolution solar map ever made of Tromsøya. The resulting solar map shows accurate results with a relative RMSE of 0.007 W/m^2 when compared against averaged pyranometer values at Holt weather station. The resulting potential from buildings on Tromsøya shows that the PV energy yield with 10% integration scenario could cover the load from Cruise ships for all summer months during the tourist season. The solar fraction (SF) shows a positive energy balance between PV energy yield and Cruise ship energy load for all months, except from March where the load was higher than yield. Calculations based on electricity spot price shows that Tromsø municipality could earn economic benefits by selling produced PV solar energy to Cruise ships